Isolated battery charger with multi‐level rectifier. Issue 14 (1st November 2016) - Wu, Jinn‐Chang; Jou, Hurng‐Liahng; Han, Jia‐Jhong
Abstract : This paper presents an isolated battery charger which is configured by a seven‐level AC‐DC power converter and an isolated DC‐DC power converter. The seven‐level AC‐DC power converter is composed of a diode rectifier and a three‐port DC‐DC power converter. The three‐port DC‐DC power converter generates a four‐level voltage at the DC bus of the diode rectifier by controlling its power electronic switches. Accordingly, the voltage at the AC input terminals of the diode rectifier is an AC voltage with seven levels, and the input current is sinusoidal and in phase with the utility voltage to perform unity power factor. The inductance of the filter inductor and the capacity of the EMI filter can be reduced due to the seven‐level AC voltage at the input AC terminals of the seven‐level AC‐DC power converter. The isolated DC‐DC power converter is a two‐level forward power converter to regulate the voltages of the three‐port DC‐DC power converter and generate an isolated output power to charge the battery set. A prototype is developed and tested to verify the performance of the isolated battery charger. The experimental results show the isolated battery charger performs as expected.